PENGARUH PEMAKAIAN PROTESA MAKSILOFASIAL DENGAN DAN TANPA HOLLOW BULB PASCA HEMIMAXILLECTOMY TERHADAP KEJELASAN SUARA - , Susi Wijiati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The causative factors of hemimaxillectomy was the existence of malignant or benign tumour at the maxilla base, congenital malformation or trauma. The effect of hemimaxillectomy is the opening space of oral cavity, nasal cavity and sinus, which named defect. To overcome the defect, maxillofacial prothesis is needed to restore the function of speech. The purpose of this study was to determine the effect of maxillofacial prosthesis with and without post-hemimaxillectomy hollow bulb on the clarity of the speech sound. Six subject was follow the criteria, with Class II Aramany defect. Speech sound was recorded when using the maxillofacial prothesis with and without hollow bulb, the subjects were ordered to say buy/bobby/puppy, and the sound recorded using cool edit software version 2.0. Data would be analyzed by t test by compairing the average frequence of the sound when used maxilofacial frequence with and without hollow bulb. The result of the t test analysis showed a significant differences between subject that used the maxilofacial prothesis with and without hollow bulb (p<0,05). The conclusion of this study was the use of post hemimaxillectomy maxillofacial prosthesis with a hollow bulb affect the increased the clarity of speech sound.